Cariprazine: An Antipsychotic Medication with High Therapeutic Potential - Wiktoria; Anna Greguła; Karol Stachyrak; Dawid Mika; Justyna Matuszewska; Bartosz Mazur; Kamila Babkiewicz-Jahn; Izabela Oleksak; Iwona Welian-Polus; Kamila Turek (Journal of Education, Health and Sport, 2024)
Introduction and purpose Cariprazine is an atypical antipsychotic drug approved for the treatment of schizophrenia, as well as manic and mixed episodes associated with bipolar disorder. It functions as a dopamine multifunctional agent, a partial agonist at dopamine and serotonin receptors. Unlike the majority of antipsychotics, which primarily target positive symptoms through dopaminergic antagonism, often neglecting negative, cognitive, and affective symptoms, the unique cariprazine's pharmacological profile, particularly potent blockade of D3 dopamine receptors, suggests the potential for numerous clinical applications. The aim of this study is to present current knowledge of cariprazine, focusing particularly on its mechanism of action, potential applications, adverse effects, and pharmacokinetic properties that could impact its clinical use. Methods and materials A review of the literature available in the PubMed database was performed using the key words: cariprazine; atypical antipsychotic drug; antipsychotic medication; schizophrenia treatment; bipolar disorder treatment; mania treatment; depression treatment, dopamine agonist. Conclusions Cariprazine demonstrates a unique pharmacological profile, offering potential benefits in managing a wide range of psychiatric disorders, including schizophrenia, bipolar disorder (mania, depression, mixed episodes), unipolar depression, and co-occurring substance use disorders. Clinical studies have shown efficacy in reducing symptoms and improving negative and cognitive function, with a favorable metabolic profile, minimal impact on cardiovascular system, and generally mild adverse effect profile. However, further research is necessary to explore its full therapeutic potential and optimize its clinical use in diverse patient populations.